2020
DOI: 10.1016/j.drugalcdep.2020.108253
|View full text |Cite
|
Sign up to set email alerts
|

Successful engagement in buprenorphine treatment among hospitalized patients with opioid use disorder and trauma

Abstract: Background:The opioid epidemic continues to cause significant morbidity and mortality. Although there are effective medications for opioid use disorder (OUD), a minority of patients receive these treatments. OUD is common among patients hospitalized for traumatic injury and hospitalization could be an opportunity to initiate medications and link to ongoing buprenorphine care.Methods: This retrospective cohort study based on electronic health record review included patients who were: (1) hospitalized between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…96 Finally, low retention in MOUDs remains a constant and unaddressed problem. Retention is fundamental to achieving successful outcomes of MOUDs, 97,98 as MOUD discontinuation may result in return to opioid use and increased overdose risk. 99,100 However, the grand majority of patients who start MOUDs discontinue in less than 6 months, the minimum recommended length of care.…”
Section: Ongoing Challengesmentioning
confidence: 99%
“…96 Finally, low retention in MOUDs remains a constant and unaddressed problem. Retention is fundamental to achieving successful outcomes of MOUDs, 97,98 as MOUD discontinuation may result in return to opioid use and increased overdose risk. 99,100 However, the grand majority of patients who start MOUDs discontinue in less than 6 months, the minimum recommended length of care.…”
Section: Ongoing Challengesmentioning
confidence: 99%
“…12,13 Some hospitals are expanding access to medications for opioid use disorder by implementing addiction consult services. 14 In addition to access to medications for opioid use disorder, addiction consult services provide counselling, medication dose titrations to long-term (versus acute) regimens, and referrals with linkage to outpatient care. 15 Many addiction consult services have restricted capacity to care for the growing number of hospitalised patients with substance use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Among included studies, the most commonly evaluated outcomes were post-discharge linkage to care (11 studies), 13 , 16 20 , 22 , 24 26 , 33 readmission (6 studies), 15 , 18 , 21 , 25 27 and in-hospital MOUD initiation (6 studies) 15 , 19 , 24 , 25 , 27 , 33 . Regarding outcome measures for the 12 studies with a control group, most studies identified outcomes through chart review 13 , 15 , 18 , 25 , 27 or diagnosis codes, 17 , 21 , 23 , 24 , 26 while others used research staff 20 including through timeline follow-back 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Among included studies, the most commonly evaluated outcomes were post-discharge linkage to care (11 studies), 13 , 16 20 , 22 , 24 26 , 33 readmission (6 studies), 15 , 18 , 21 , 25 27 and in-hospital MOUD initiation (6 studies) 15 , 19 , 24 , 25 , 27 , 33 . Regarding outcome measures for the 12 studies with a control group, most studies identified outcomes through chart review 13 , 15 , 18 , 25 , 27 or diagnosis codes, 17 , 21 , 23 , 24 , 26 while others used research staff 20 including through timeline follow-back 34 . Wang and colleagues defined linkage to care as when a provider discharged a patient with a buprenorphine prescription and a scheduled outpatient buprenorphine appointment, 25 while others defined it as post-hospital OUD treatment engagement 18 , 24 , 34 within 30, 13 , 20 34, 17 or 90 days 20 .…”
Section: Resultsmentioning
confidence: 99%